OPTIMIZATION OF CULTURAL CONDITIONS FOR CHITINASE PRODUCTION FROM CHITINOLYTIC BACTERIUM ISOLATED FROM SOIL SAMPLE. - RIDDHI J. JHOLAPARA; RADHIKA S.MEHTA; CHHAYA S. SAWANT (International Journal of Pharma and Bio Sciences, 2013)
Chitinases are group of enzymes which play a significant role in degrading chitin. The present study explores the natural ability of the bacteria to utilize chitin as a source of energy. Soil samples were screened for chitinolytic organisms and strain which produced highest chitinolytic activity was selected. Biochemical analysis revealed that the isolate belongs to the genus Bacillus. It was identified upto the species level as Bacillus licheniformis, using 16S rRNA based identification system. The cultural conditions for production of chitinase was optimized which resulted in a significant increase in the enzyme activity. The study demonstrates the potential of the isolate for industrial application such as production of bioactive chitin-oligosachharides.